Multipoint problem with for factorized parabolic operator with variable coefficients - Tymkiv, I.R. (Carpathian Mathematical Publications, 2011)
The correctness of the problem with multipoints conditions with respect time-variable and conditions of the Dirichlet by Petrovski linear parabolic equation with variable coefficients in a limited cylindrical domen. The conditions of existence and uniqueness of the classical solution of the problem are established. The metrical theorems on evalution from below of small denominators of the problem are proved.